2020
DOI: 10.1055/s-0040-1718574
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on the Management and Outcomes of Postpartum Hemorrhage

Abstract: Objective The study aimed to evaluate the impact of obesity on the management and outcomes of postpartum hemorrhage. Study Design We conducted a retrospective cohort study of women who delivered at a tertiary care center between February 1, 2013 and January 31, 2014 and experienced a postpartum hemorrhage. Charts were reviewed for clinical and sociodemographic data, and women were excluded if the medical record was incomplete. Hemorrhage-related severe morbidity indicators included blood transfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…39 The observed link between obesity and PPH, as reported in our study, has been attributed to the increased risk of cesarean section and the impaired uterine response to control bleeding due to the possible disruption of the hormonal balance in obese women. 40 Similar to our study, previous studies have reported that women with a previous history of PPH have up to three-fold higher risk of PPH. 41,42 This could be explained by the presence of chronic comorbidities that are known risk factors for PPH, such as hypertensive disorders in pregnancy and uterine fibroids or genetic or environmental factors that affect the risk of PPH throughout pregnancy.…”
Section: Characteristics N (%)supporting
confidence: 92%
“…39 The observed link between obesity and PPH, as reported in our study, has been attributed to the increased risk of cesarean section and the impaired uterine response to control bleeding due to the possible disruption of the hormonal balance in obese women. 40 Similar to our study, previous studies have reported that women with a previous history of PPH have up to three-fold higher risk of PPH. 41,42 This could be explained by the presence of chronic comorbidities that are known risk factors for PPH, such as hypertensive disorders in pregnancy and uterine fibroids or genetic or environmental factors that affect the risk of PPH throughout pregnancy.…”
Section: Characteristics N (%)supporting
confidence: 92%
“… 19 Another study suggest that obese women had higher quantities of blood loss, required more transfused blood units and had more severe morbidity although they had the same management as those with normal BMI. 20 …”
Section: Discussionmentioning
confidence: 99%
“…19 Another study suggest that obese women had higher quantities of blood loss, required more transfused blood units and had more severe morbidity although they had the same management as those with normal BMI. 20 However, debate is still ongoing on other such outcomes resulting from pre-pregnancy obesity or obesity occurring throughout pregnancy. Studies described how obesity might predispose for maternal and fetal illnesses either before or during pregnancy.…”
mentioning
confidence: 99%
“…In Present study PPH was more common in women with LSCS (69.2%) compared to vaginal delivery (30.8%) which is in contrast with the observation made by Blomberg M [8] and Usha Kiran TS et al [22] where a small increased risk among obese women following vaginal delivery was observed. Polic A et al in their study observed that obese women were more likely to deliver by cesarean section (55.5 vs. 39.8%, p = 0.016) and were more likely to have a higher quantitative blood loss and require more units of blood transfusion and had more severe morbidity although they had the same management as those with normal BMI [23].…”
Section: Discussionmentioning
confidence: 92%